Navigating Indigene-Settler Conflicts in Fako Division, Cameroon (African Journal of Law and Politics, 2025)
This study investigates the drivers, management strategies, and challenges of indigene-settler conflictsin Fako Division, Cameroon, a region marked by historical colonial legacies, rapid demographicchange, and socio-political complexity. Adopting a qualitative methodology, the research draws onsemi-structured interviews with seventeen purposively selected participants, including traditionalleaders, government officials, civil society actors, and community members from both indigene andsettler backgrounds. Thematic analysis reveals that disputes over land ownership deeply intertwinedwith identity and cultural heritage are the primary source of conflict, exacerbated by culturalmisunderstandings, political manipulation, and economic rivalry. Traditional authorities are widelyregarded as the most trusted mediators, while formal legal and state mechanisms are often perceived asslow, biased, and lacking legitimacy. Community-based organizations and NGOs contribute positively,especially in peace education, but their impact is limited by resource constraints and inconsistentengagement. Key obstacles to effective conflict management include ambiguous land tenure laws,political interference, weakened traditional institutions, and the exclusion of youth and women frompeace processes. The study concludes that sustainable peace in Fako Division requires a holistic, multi-stakeholder approach that integrates traditional and formal systems, strengthens community-basedmechanisms, reforms land governance, and actively involves marginalized groups. These findingscontribute to a broader understanding of identity-based conflicts in postcolonial African societies andinform policy recommendations for inclusive and context-sensitive peacebuilding.